2021
DOI: 10.5194/wcd-2021-45
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synoptic processes of winter precipitation in the Upper Indus Basin

Abstract: Abstract. Precipitation in the Upper Indus Basin is triggered by cross-barrier moisture transport. Winter precipitation events are particularly active in this region and are driven by an approaching upper troposphere Western Disturbance. Here statistical tools are used to decompose the winter precipitation timeseries into a wind and a moisture contribution. The relationship between each contribution and the Western Disturbances are investigated. We find that the wind contribution is not only related to the int… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It is known that both the latitude of the subtropical jet (Hunt et al, 2017) and its intensity (Hunt et al 2018) exert controls on WD behaviour over South Asia. In addition, the greater vertical wind shear exerted by a stronger jet is associated with more intense updrafts in WDs (Baudouin et al, 2021). As the NAO affects both of these jet characteristics, we can reasonably hypothesise that it will also modulate downstream WD behaviour.…”
Section: The Spectral Relationship Between the Nao And Wdsmentioning
confidence: 80%
“…It is known that both the latitude of the subtropical jet (Hunt et al, 2017) and its intensity (Hunt et al 2018) exert controls on WD behaviour over South Asia. In addition, the greater vertical wind shear exerted by a stronger jet is associated with more intense updrafts in WDs (Baudouin et al, 2021). As the NAO affects both of these jet characteristics, we can reasonably hypothesise that it will also modulate downstream WD behaviour.…”
Section: The Spectral Relationship Between the Nao And Wdsmentioning
confidence: 80%
“…As our findings suggest an enhancement in both transient activity of westerly troughs and moisture flux convergence, it can be concluded that variability in dynamic responses of the atmosphere in conjunction with thermodynamic variations might be a major contributing factor for increasing trends of extreme precipitation over the region. Mediterranean, Caspian, Red and Arabian seas are primary contributors for eastward moisture advection towards WH leading to moisture availability for precipitation [74,75]. Here, we have tried to investigate the trends for winter seasonal moisture supply over WH (Figure 5n) through time series for VIMT which reveals a clear increasing trend in the moisture transport over WH through the years.…”
Section: Winter Seasonmentioning
confidence: 99%
“…Contrasting trends were observed in the frequency and intensity of extratropical disturbances in WH (Cannon et al ., 2015; Yadav et al ., 2017; Hunt et al ., 2019). Nevertheless, due to the topography, these disturbances are sustained in WH by their interaction with low‐level winds whereas they decay quickly in CH/EH (Baudouin et al ., 2021). Therefore, the meteorological processes that influence precipitation in the WH are distinct from those in the CH or the EH; hence, these processes must be categorized and studied independently.…”
Section: Introductionmentioning
confidence: 99%